Anatomy and evolution of the head of Dorylus helvolus (Formicidae: Dorylinae): Patterns of sex‐ and caste‐limited traits in the sausagefly and the driver ant. (12th September 2021) - Boudinot, Brendon Elias; Moosdorf, Olivia Tikuma Diana; Beutel, Rolf Georg; Richter, Adrian
Abstract: Ants are highly polyphenic Hymenoptera, with at least three distinct adult forms in the vast majority of species. Their sexual dimorphism, however, is overlooked to the point of being a nearly forgotten phenomenon. Using a multimodal approach, we interrogate the near total head microanatomy of the male of Dorylus helvolus, the "sausagefly, " and compare it with the conspecific or near‐conspecific female castes, the "driver ants." We found that no specific features were shared uniquely between the workers and males to the exclusion of the queens, indicating independence of male and worker development; males and queens, however, uniquely shared several features. Certain previous generalizations about ant sexual dimorphism are confirmed, while we also discover discrete muscular presences and absences, for which reason we provide a coarse characterization of functional morphology. Based on the unexpected retention of a medial carinate line on the structurally simplified mandible of the male, we postulate a series of developmental processes to explain the patterning of ant mandibles. We invoke functional and anatomical principles to classify sensilla. Critically, we observe an inversion of the expected pattern of male‐queen mandible development: male Dorylus mandibles are extremely large while queen mandibles are poorly developed. To explain this, we posit that the reproductive‐limited mandible phenotype is canalized in Dorylus, thus partially decoupling the queen and worker castes. We discuss alternative hypotheses and provide further comparisons to understand mandibular evolution in army ants. Furthermore, we hypothesize that the expression of the falcate phenotype in the queen is coincidental, that is, a "spandrel, " and that the form of male mandibles is also generally coincidental across the ants. We conclude that the theory of ant development and evolution is incomplete without consideration of the male system, and we call for focused study of male anatomy and morphogenesis, and of trait limitation across all castes. Abstract : The sexual dimorphism of ants is understudied, relative to the within‐sex polyphenism of females. Through comparison of male and female Dorylus, we discovered that the reproductives share specific head features to the exclusion of workers—a previously unrecorded phenomenon which suggests that there is an additional axis of morphogenetic variation in ants. We further address mandibular development, muscle morphology, sensilla patterning, and provide the first anatomical atlas of the head of male Formicidae.